Social Determinants of Health Curriculum Integrated Into a Core Emergency Medicine Clerkship - Shannon E. Moffett; Hosseinali Shahidi; Harsh Sule; Sangeeta Lamba (Association of American Medical Colleges, 2019)
Introduction Demand that health centers address health inequities has led medical schools to emphasize social determinants of health (SDH). The Emergency Department often serves as first (or sole) point of health care access, making it an ideal environment in which to identify/explore SDH. Yet there are few SDH curricula targeting core emergency medicine (EM) clerkships. We describe implementation and outcomes of a three-part SDH curriculum instituted in a 4-week EM clerkship. Methods We created a longitudinal curriculum aimed at fourth-year medical students in their EM clerkship. Students interviewed patients to discuss social and other influences on their health care and wrote reflections. After this, they discussed their individual cases in small groups, selected one patient, and found literature and strategies/systems to fit the patient's needs. Finally, groups presented their work to student-peers and faculty for discussion. Students were assessed for each activity and surveyed for impact of the curriculum. Results We evaluated the curriculum, with preliminary data showing a wide range of topics covered. On a 5-point scale (1 = Hardly at All, 5 = To a Very High Degree), students responded with means of 4.4 to "I am able to recognize barriers to health that patients and families face from diverse socio-economic backgrounds" and 4.6 to "I feel it is important to recognize and address the social determinants of health as part of whole patient care." Discussion This curriculum introduces SDH, uses metacognitive skills across multiple domains, and is feasible and has been well received in an EM clerkship.